Diskresi Hukum Administrasi dalam Perlindungan Hak Ekonomi Nelayan Tanpa Surat Izin Penangkapan Ikan - Putra, Diki Okta Dwi; Sembiring, Oktavianus Abrianta; Simamarta, Anggi Sri Haryati (Jurnal Litigasi Amsir, 2025)
This study analyzes the role of administrative law in addressing bureaucratic complexities within Indonesia’s fishing licensing system, specifically the issuance of the Fishing Vessel License (Surat Izin Penangkapan Ikan/SIPI). The normative legal approach highlights the tension between regulatory demands and practical challenges faced by fishermen. Despite the existence of clear legal provisions mandating fishing permits, implementation remains hindered by prolonged bureaucratic processes, limited information access, and inadequate administrative capacity. These obstacles have caused significant economic and social impacts on local fishing communities. The study finds that administrative discretion, when applied responsibly, may serve as a remedial mechanism to bridge regulatory gaps and support sustainable livelihood governance. However, its exercise must align with the principles of legal certainty, accountability, and public benefit under the framework of good governance to ensure justice and legal consistency in fisheries administration.